Serum Osteocalcin Is Associated with Inflammatory Factors in Metabolic Syndrome: A Population-Based Study in Chinese Males - Ming Liao; Lirong Huang; Yan Mao; Yonghua Jiang; Ziting Yao; Xinggu Lin; Zheng Lu; Chunlei Wu; Xue Qin; Haiying Zhang; Zengnan Mo (Mediators of Inflammation)
Osteocalcin (OCN) was potentially associated with inflammatory factors, so we explored the metabolic role in this association in general population. Our findings suggest that OCN was positively associated with IgG while inversely associated with C3, both of which were probably mediated by obesity. Moreover, serum OCN was inversely associated with hsCRP in men with impaired fasting glucose, hyperglycemia, or metabolic syndrome, while its association with IgE was significantly observed in men with a normal metabolic profile.